2016
DOI: 10.1017/s0022215116009658
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of steroidal vs non-steroidal agents in oral lichen planus: a randomised, open-label study

Abstract: Non-steroidal drugs such as dapsone, tacrolimus and retinoid are as efficacious as steroidal drugs for treating oral lichen planus, and avoid the side effects associated with steroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 24 publications
0
34
0
3
Order By: Relevance
“…Two additional articles were identified by manual searching . Finally, 21 RCTs were included in the analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two additional articles were identified by manual searching . Finally, 21 RCTs were included in the analysis (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
“…The time range to evaluate relapse was 2 weeks to 6 months after drug discontinuance. After excluding the studies with unavailable numbers of patients with relapse and no relapse during the observation period, four studies (240 patients) showed no significant difference between tacrolimus and TCS (RR 1·02, 95% CI 0·38–2·72, I 2 = 68%). There was also no material change in the overall combined RR after excluding any single study (range: RR 0·68, 95% CI 0·25–1·81 to RR 1·70, 95% CI 0·93–3·12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous invasive and non‐invasive therapeutic methods including local/systemic corticosteroids, laser therapy, and surgical intervention for the treatment of OLP are suggested . Cutaneous lesions generally improve spontaneously after therapy; however, OLP requires protracted treatment through steroids and long‐term follow‐up .…”
Section: Introductionmentioning
confidence: 99%
“…5 Numerous invasive and non-invasive therapeutic methods including local/systemic corticosteroids, laser therapy, and surgical intervention for the treatment of OLP are suggested. [6][7][8] Cutaneous lesions generally improve spontaneously after therapy; however, OLP requires protracted treatment through steroids and long-term follow-up. 9 Extended use of corticosteroids for chronic OLP may have certain local and systemic complications, which includes opportunistic candidiasis, mucosal atrophy, adrenal insufficiency, gastrointestinal disorders, hypertension, and diabetes.…”
Section: Introductionmentioning
confidence: 99%